PENERBITAN JURNAL ILMIAH UNTUK MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA - B. P. Sitepu (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
Scientific journal is one of the periodical publications intended to widely disseminate research findings useful for research and academic communities. Articles published in the journal tend to be highly technical, representing the latest theoretical research and experimental results in the field of science, technolgy, or arts covered by the journal. Articles in the journal can be used as references and inspire researchers and scholars to do further researh. The quantity and quality of journals in a country can indicate the quality of the human resource and development of science, technology, and arts in the country. Based on the available data, the quantity and the quality of journal in Indonesia are still unsatisfactory. This article discusses some problems in managing journal and provides a number of recommendation which are useful for those publishing a journal.